Gamer girl - Mancusi, Mari (Dutton Children's Books, 2008)
Struggling to fit in after her parents' divorce sends her from Boston to her grandmother's house in the country, sixteen-year-old Maddy forms a manga club at school and falls in love through an online fantasy game.